2004
DOI: 10.1111/j.1460-9568.2004.03208.x
|View full text |Cite
|
Sign up to set email alerts
|

AMPA receptor properties and coexpression with sodium–calcium exchangers in rat hypothalamic neurons

Abstract: The histaminergic tuberomamillary (TM) nucleus, a center for the regulation of wakefulness, is excited by glutamatergic, aminergic and peptidergic inputs. AMPA receptor properties in relation to their expression were investigated in acutely isolated TM neurons with the help of whole-cell patch-clamp recordings combined with single-cell RT-PCR. The mRNAs encoding for the AMPA receptor GluR2 (100% of the neurons) and GluR1 (75%) were the most frequently detected, followed by the mRNA for GluR4 (56%), whereas Glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…It was shown previously that the prevailing expression of flop-splice variants of GluRs contributes to the faster desensitization of these receptors (Audinat et al 1996). In accordance, we have shown that GluR4-flop expression in TMN neurons coincides with the very fast desensitization of glutamate responses (Sergeeva et al 2004). Therefore, flop-expressing cells were excluded from the present study (n = 4).…”
Section: Analysis Of Adar Expressionsupporting
confidence: 71%
See 3 more Smart Citations
“…It was shown previously that the prevailing expression of flop-splice variants of GluRs contributes to the faster desensitization of these receptors (Audinat et al 1996). In accordance, we have shown that GluR4-flop expression in TMN neurons coincides with the very fast desensitization of glutamate responses (Sergeeva et al 2004). Therefore, flop-expressing cells were excluded from the present study (n = 4).…”
Section: Analysis Of Adar Expressionsupporting
confidence: 71%
“…Splice variants of AMPA receptors were analyzed by the restriction analysis (see Vorobjev et al 2000). In all investigated neurons the GluR4 subunit was present in the flip isoform (GluR4-flop expressing cells (see Sergeeva et al 2004) were rare and they were excluded from the study). The Q/R site-containing cDNA fragment was amplified in the second round with the Q/Rup: 5 0 -GGA AGA GAA ACA CAA AGT AGT G-3 0 and Q/Rlo: 5 0 -TTT GCT TAG ACA GAT CCT CAG C-3 0 primers.…”
Section: Animals and Tissue Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Serotonin depolarizes histamine neurons and increases their firing rate by activation of 5-HT 2C receptors and a NCX1 Na þ /Ca 2 þ exchanger [379,380]. Glutamatergic a-amino-3-hydroxy-5-methyl-4-isoxazole propinoic acid (AMPA) receptors coexpressed with NCKX Na þ /Ca 2 þ exchangers activate acutely isolated histamine neurons with different desensitization properties [381]. Although a purinergic transmission in the tuberomammillary nucleus has not yet been reported, adenosine triphosphate (ATP) can be coreleased with different transmitters such as GABA and excites individual histaminergic neurons through P2X receptors [382,383].…”
Section: Modulation Of Histaminergic Neuron Activity In Vitromentioning
confidence: 99%